2000
DOI: 10.1073/pnas.190066697
|View full text |Cite
|
Sign up to set email alerts
|

Leptin as a modulator of sweet taste sensitivities in mice

Abstract: Leptin acts as a potent inhibitory factor against obesity by regulating energy expenditure, food intake, and adiposity. The obese diabetic db͞db mouse, which has defects in leptin receptor, displays enhanced neural responses and elevated behavioral preference to sweet stimuli. Here, we show the effects of leptin on the peripheral taste system. An administration of leptin into lean mice suppressed responses of peripheral taste nerves (chorda tympani and glossopharyngeal) to sweet substances (sucrose and sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
278
7
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(306 citation statements)
references
References 34 publications
(39 reference statements)
17
278
7
3
Order By: Relevance
“…Whole nerve responses to lingual application of tastants were recorded from the CT and the GL nerve as described (9,15,16). Responses to tastants were normalized to responses to NH 4 Cl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole nerve responses to lingual application of tastants were recorded from the CT and the GL nerve as described (9,15,16). Responses to tastants were normalized to responses to NH 4 Cl.…”
Section: Methodsmentioning
confidence: 99%
“…RT-PCR and immunostaining were as described previously (9,10). Primer sequences for each PCR are listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Leptin modulates sweet taste sensation via actions on sweet taste receptor cells via the leptin receptor. Increased leptin decreases firing of sweet taste cells in mice (Kawai et al, 2000).…”
Section: A Role For Cephalic Phase Responses In Appetite and Satiety?mentioning
confidence: 98%
“…Injection of leptin into lean mice resulted in suppressed response to sweet tastants in peripheral taste nerves without effect on other taste qualities. 80 Shigemura et al 81 demonstrated that the functional leptin receptor Ob-Rb messenger RNA is expressed in the fungiform and circumvallate taste buds in mice and that the presence or absence of Ob-Rb was associated with differences in leptin's effect on behavioral response to sweet substances. Leptin receptor-deficient obese mice showed increased gustatory neural response to sweet compounds.…”
Section: Leptinmentioning
confidence: 99%